Adsorpsi Logam Merkuri (Hg) dari Limbah Tanah Tercemar Menggunakan Tanaman Sawi (Brassica juncea L) pada Berbagai Waktu Tanam: Adsorption of Mercury (Hg) from Contaminated Soil Waste Using Sawi Plants (Brassica juncea L) in Various Planting Times - Khairuddin; Wiranto Wengkau; Dwi Juli Puspitasari; Husain Sosidi; Nov Irmawati Inda (KOVALEN: Jurnal Riset Kimia, 2021)
Mercury (Hg) as a gold extractor can cause environmental pollution, therefore, hyperaccumulator plants are needed, such as mustard greens (Brassica juncea L). Research on the effect of planting time of mustard greens on the adsorption of mercury (Hg) metal ion on contaminated soil waste has been carried out. The purpose of this research was to determine the concentration and adsorption mechanism of Hg metal ion from contaminated soil at roots and canopy of mustard plants at various planting times. Amount of Hg metal ion adsorbed on the roots and canopy of mustard greens at 2, 4, and 6 weeks of planting times were analyzed using Atomic Absorption Spectrophotometry (AAS). The results showed that the average levels of Hg metal ion adsorption at various planting time of 2, 4, and 6 weeks at roots were 156.611 μg/g, 810.256 μg/g, and 888.711 μg/g, respectively, and at the canopy were 69.486 μg/g, 134.580 μg/g, and 60.416 μg/g, respectively. The planting time of 6 weeks resulted in the highest adsorption ability of Hg at the roots. The results of the bioconcentration factor (BCF) test showed that the adsorption of Hg in the roots and canopy of the mustard plant took place using a phytoextraction mechanism (BCF < 1).